Case report: The CCDC103 variant causes ultrastructural sperm axonemal defects and total sperm immotility in a professional athlete without primary ciliary diskinesia - Luongo, Francesca Paola; Luddi, Alice; Ponchia, Rosetta; Ferrante, Rossella; Di Rado, Sara; Paccagnini, Eugenio; Gentile, Mariangela; Lupetti, Pietro; Guazzo, Raffaella; Orrico, Alfredo; Stuppia, Liborio; Piomboni, Paola (Frontiers in Genetics, 2023)
Primary ciliary dyskinesia (PCD) is an inherited autosomal-recessive disorder characterized by abnormal ciliary motion, due to a defect in ciliary structure and/or function. This genetic condition leads to recurrent upper and lower respiratory infections, bronchiectasis, laterality defect, and subfertility. Male infertility is often associated with PCD, since the ultrastructure of the axoneme in the sperm tail is similar to that of the motile cilia of respiratory cells. We present the first reported case of a male patient from a non-consanguineous Italian family who exhibited a severe form of asthenozoospermia factor infertility but no situs inversus and absolutely no signs of the clinical respiratory phenotype, the proband being a professional basketball player. Whole-exome sequencing (WES) has identified a homozygote mutation (CCDC103 c.461 A>C, p.His154Pro) in the proband, while his brother was a heterozygous carrier for this mutation. Morphological and ultrastructural analyses of the axoneme in the sperm flagellum demonstrated the complete loss of both the inner and outer dynein arms (IDA and ODA, respectively). Moreover, immunofluorescence of DNAH1, which is used to check the assembly of IDA, and DNAH5, which labels ODA, demonstrated that these complexes are absent along the full length of the flagella in the spermatozoa from the proband, which was consistent with the IDA and ODA defects observed. Noteworthy, TEM analysis of the axoneme from respiratory cilia showed that dynein arms, although either IDAs and/or ODAs seldom missing on some doublets, are still partly present in each observed section. This case reports the total sperm immotility associated with the CCDC103 p.His154Pro mutation in a man with a normal respiratory phenotype and enriches the variant spectrum of ccdc103 variants and the associated clinical phenotypes in PCD, thus improving counseling of patients about their fertility and possible targeted treatments.